Two crystal structures of copper(II) complexes and adducts based on the neutral N1,N1-dimethyl-N2-(pyridin-2-ylmethyl)ethane-1,2-diamine ligand - Basam M. Alzoubi; Carola Schulzke (Acta Crystallographica Section E: Crystallographic Communications)
From the reaction of copper(II) chloride dihydrate with N1,N1-dimethyl-N2-(pyridin-2-ylmethyl)ethane-1,2-diamine (denoted N^N^N) a new species comprising three distinct complexes crystallized, namely, aquachlorido[N1,N1-dimethyl-N2-(pyridin-2-ylmethyl)ethane-1,2-diamine-κ3N,N′,N′′]copper(II) chlorido[N1,N1-dimethyl-N2-(pyridin-2-ylmethyl)ethane-1,2-diamine-κ3N,N′,N′′]copper(II) tetrachloridocuprate(II), [CuCl(C10H17N3)(H2O)][CuCl(C10H17N3)][CuCl4] or [Cu(N^N^N)(H2O)Cl][Cu(N^N^N)Cl2][CuCl4], the latter two of which form an adduct. This complex was reacted with ammonium thiocyanate to form [Cu(N^N^N)(NCS)2], which crystallized with two independent molecules and a partial water in the asymmetric unit very similarly to the already reported structure of this compound. Both crystal structures show a rather complex set of intermolecular interactions including hydrogen bonding and what may be described as chalcogen bonding, pnictogen bonding and/or coinage bonding. The molecular structures, intramolecular interactions and packing patterns are discussed in detail and the more unusual ones are set into the context of structures available in the literature.